A agroindústria familiar rural e a produção de queijos artesanais no município de Seara, Estado de Santa Catarina - um estudo de caso - Carvalho, Michelle de Medeiros (2015)
In the name of food policy, the processing and marketing of Artisanal Cheese made from raw milk have been inhibited by the action of regulatory agencies, which have been demanding pasteurization of milk for the manufacture of cheese as a solution to ensure product safety. A specific legislation for raw milk cheese production was recently published to meet various requirements of society in defense of Artisanal Cheese. The aim of this study was to investigate the situation of 12 rural properties in Seara-SC that were producing and selling Artisanal Colonial-Type Cheese informally. Producers were visited and their conditions for obtaining water, performing milking and making cheese were assessed. A semi-structured questionnaire was used to analyze the difficulties faced by farmers in compliance with current legislation for artisanal raw milk cheese production. Physical, chemical and microbiological analyzes of water, milk and cheese were conducted to check the adequacy of legal standards. It was found that none of the Colonial cheese makers investigated met the requirements established by law for Artisanal Cheese production from raw milk. Among the samples of water, milk and cheese analyzed, 91.7% (n = 11), 50% (n = 6) and 100% (n = 12), respectively, were found outside the legal parameters. It was concluded that cheese makers were unable to meet the requirements set by law, without some technical support, because they were difficult to be applied by them. They often need guidance and do not know where to seek orientation to meet all legal specifications. This study also concluded that public policies need to be employed for the preservation of Artisanal Colonial-Type Cheese, considering its historical and socio-economic relevance for family farming, to preserve the cultural tradition of such communities